Molecular characterization of Sweet potato feathery mottle virus and sweet potato yield loss due to its infection - GUSTI NGURAH ALIT SUSANTA WIRYA; DEWA GEDE WIRYANGGA SELANGGA; LISTIHANI LISTIHANI; I GEDE RAI MAYA TEMAJA; I PUTU SUDIARTA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Wirya GNAS, Selangga DGW, Listihani L, Temaja IGRM, Sudiarta IP. 2024. Molecular characterization of Sweet potato feathery mottle virus and sweet potato yield loss due to its infection. Biodiversitas 25: 2355-2362. Sweet potatoes are one of the main sources of carbohydrates for Balinese. "Nasi selo," one of Bali's specialties, uses sweet potato as one of its main ingredients. For the past few years, cultivated sweet potatoes in Bali, Indonesia, manifested symptoms of diseases, particularly purple ring spots, occurring on its young and old leaves. The causative agent of the purple ring symptom is still unknown. Therefore, this study aims to analyze the molecular characteristics of SPFMV Bali isolate and the yield loss estimation it causes. Research methods that were used in this study are survey, sampling, virus identification with RT-PCR using universal Potyvirus as its primer, and field observation to assess the yield loss estimation. Field observation was conducted in five districts in Bali province: Badung, Gianyar, Bangli, Karangasem, and Klungkung. The result indicates that SPFMV infection has been found in these 5 districts, with the highest incidence and severity occurring in Bangli at 86% and 53%. The nucleotide homology of the SPFMV Bali isolates gene has the closest genetic relationship with isolates found in South Korea (MH388494, MH388494) and East Timor (MF572056), at >99%. Based on the latest phylogroup classification, SPFMV is categorized into phylogroups A and B. Phylogroup A consists of SPFMV with O-I strain, O-II strain, and EA strain; phylogroup B only consists of SPFMV with RC strain. Isolate SPFMV found in Bali, has an O strain that belongs to the same group as the O-I strain, also seen in South Korea, East Timor, and China. Actual yield loss that was found by comparing sweet potatoes suffering from purple rings symptom with the one without purple rings symptom reveals a yield loss of 50.9%. Harvested sweet potatoes with purple ring symptoms showed quality deterioration in malformation, discoloration, hollowing, and changes in color and shape. Yield loss of up to 29.53% in fields with a disease severity of 53% has caused a loss of IDR 2,105,166.